Entornos Virtuales Lúdicos en el Aprendizaje del Ámbito Lógico - Matemático en Niños de Educación Inicial 2 del Centro de Educación Inicial la Primavera Cantón Riobamba - Sayay Herrera, Mishell Carolina (2025)
The present research, "Playful Virtual Environments in Logical-Mathematical Learning for Children in Early Childhood Education Level 2 at the La Primavera Early Childhood Education Center, Riobamba Canton," aims to analyze the impact of using playful environments on logical-mathematical learning in children in Early Childhood Education Level 2 at the institution. To better understand the research topic, a qualitative methodology with a non-experimental design was employed, as it observes the development of logical-mathematical learning in a real-world context without altering the variables of their environment. This is a basic and descriptive study. It also includes field research, which involved applying an observation checklist to a population of 30 children in Early Childhood Education Level 2. The results of this study recommend integrating digital strategies into early childhood education, accompanied by teacher training and policies to ensure equitable access to technology and guarantee high-quality, engaging learning experiences. Thus, it is concluded that virtual play environments strengthen meaningful